The Relationship between the Prohibitions of Abuse of Dominance and Vertical Restraints - Noda Yamada, Carlos (2006)
A competitive market is a mechanism that distributes resources among consumers to satisfy their needs. Competition among companies plays a crucial role in this process because it seeks to maximize consumer welfare. For this reason, it is essential that laws protect competition, since their purpose is to promote general welfare through a fairer market, preventing, for example, companies with greater market power from using it abusively or prohibiting agreements that restrict, distort or limit competition between companies. In this context, this paper examines the interaction between the prohibition of abuse of dominant position and the prohibition of anticompetitive vertical agreements, as regulated by Legislative Decree 701.